2021
DOI: 10.1002/mnfr.202000845
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Human Milk Derived Exosomes and Their Emerging Roles in the Prevention of Necrotizing Enterocolitis

Abstract: Scope: Human milk can prevent the development of necrotizing enterocolitis (NEC). Human milk is rich in cargo-carrying exosomes that participate in intercellular communication. This study investigated the effects of term and preterm human milk-derived exosomes, and elucidated their lipid expression profiles. Methods and Results: Milk from healthy mothers is collected who have delivered full-term or preterm infants, and exosomes are isolated and quantified. Administration of term and preterm milk exosomes signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…These effects were independent of the delivery status [ 126 ]. Other authors have reported similar effects of HME on the incidence and severity of NEC in rat models [ 70 , 127 ]. In particular, Chen et al observed that HME isolated from women who gave birth to term or preterm newborns exerted a protective effect on NEC by decreasing the severity of the injury and stimulating the proliferation and migration of intestinal epithelial cells independently of the delivery status [ 70 ].…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthsupporting
confidence: 54%
See 4 more Smart Citations
“…These effects were independent of the delivery status [ 126 ]. Other authors have reported similar effects of HME on the incidence and severity of NEC in rat models [ 70 , 127 ]. In particular, Chen et al observed that HME isolated from women who gave birth to term or preterm newborns exerted a protective effect on NEC by decreasing the severity of the injury and stimulating the proliferation and migration of intestinal epithelial cells independently of the delivery status [ 70 ].…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthsupporting
confidence: 54%
“…Other authors have reported similar effects of HME on the incidence and severity of NEC in rat models [ 70 , 127 ]. In particular, Chen et al observed that HME isolated from women who gave birth to term or preterm newborns exerted a protective effect on NEC by decreasing the severity of the injury and stimulating the proliferation and migration of intestinal epithelial cells independently of the delivery status [ 70 ]. The authors further analyzed the lipidomic profile of HME, finding that term and preterm milk exosomes displayed almost identical lipid compositions.…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthsupporting
confidence: 54%
See 3 more Smart Citations